2021
DOI: 10.1016/j.bonr.2021.101065
|View full text |Cite
|
Sign up to set email alerts
|

Alterations to the gut microbiome impair bone tissue strength in aged mice

Abstract: Whole bone strength and resistance to fracture are determined by a combination of bone quantity and bone quality – key factors in determining risk for osteoporosis and age-related fractures. Recent preclinical studies have shown that alterations to the gut microbiome can influence bone quantity as well as bone tissue quality. Prior work on the gut microbiome and bone has been limited to young animals, and it is unknown if the gut microbiome can alter bone tissue strength in aged animals. Here we ask if alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Diet modification and exercise are among the two most beneficial and conservative treatment approaches. Studies in rodents show promising results for the addition of high-fiber diets and the resultant increase in the gut microbiome production of short-chain fatty acids (SCFA), particularly butyrate [14], the primary metabolites of microbial fermentation in the gut [29]. SCFAs appear to protect against postmenopausal and inflammatory bone loss, repair intestinal barriers, and prevent the development of osteoporosis in mice [30][31][32].…”
Section: Lifestyle Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diet modification and exercise are among the two most beneficial and conservative treatment approaches. Studies in rodents show promising results for the addition of high-fiber diets and the resultant increase in the gut microbiome production of short-chain fatty acids (SCFA), particularly butyrate [14], the primary metabolites of microbial fermentation in the gut [29]. SCFAs appear to protect against postmenopausal and inflammatory bone loss, repair intestinal barriers, and prevent the development of osteoporosis in mice [30][31][32].…”
Section: Lifestyle Modificationsmentioning
confidence: 99%
“…Based on the abundance of metabolite and cell signaling molecules, particularly short-chain fatty acids such as butyrate [13], produced by the gut microbiota, it stands to reason that these states of unbalance may be connected and should be investigated. Furthermore, preclinical animal models have shown that alterations in the gut microbiota can decrease the quality and hence the strength of bone tissue [14], and in germ-free mice (i.e., mice without a gut microbiota), the number of osteoclasts was reduced, leading to increased bone mass [15].…”
Section: Introductionmentioning
confidence: 99%
“… 39 Previous studies have shown that the bone strength is not affected by long‐term low‐glycemic diet containing antibiotics, but GM is significantly changed. 40 Here, we report that the bacterial community richness and evenness are lower in the faecal samples from ethanol and antibiotics treated rats using the Chao1 estimator. Moreover, the differences in bacterial community structure are further investigated by PCoA and ANOSIM, indicating the differences in the structure and composition of GM among groups, which highlights the induction of GM dysbiosis in chronic heavy ethanol consumption.…”
Section: Discussionmentioning
confidence: 85%
“…Meanwhile, antibiotics are applied in rats for 16 weeks as a GM dysbiosis matched group, which has been proven to reduce taxonomic richness and diversity and influence the abundance of bacterial taxa in faeces 39 . Previous studies have shown that the bone strength is not affected by long‐term low‐glycemic diet containing antibiotics, but GM is significantly changed 40 . Here, we report that the bacterial community richness and evenness are lower in the faecal samples from ethanol and antibiotics treated rats using the Chao1 estimator.…”
Section: Discussionmentioning
confidence: 99%
“…Bone is impacted by gut microbial dysbiosis that both impairs the intestinal absorption of calcium and dysregulates osteoclasts’ activity via the serum levels of insulin-like growth factor 1 (IGF-1) [ 17 ]. Moreover, microbiota alterations also reduce bone strength and quality [ 18 , 19 ], and affect the OPG/RANKL pathway in osteoclasts [ 20 ]. Furthermore, dysbiosis in mice also interferes with skeletal muscle mass and physical performance, altering the production of rapsyn and Lrp4—two crucial proteins in the functioning of neuromuscular junctions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%